Lived Experiences on Data Gathering of Development Studies Graduate and Post-Graduate Students in a Hybrid Learning Environment - Tautho, Dana Gabrielle B.; Zuyco, Quennie Marie S.; Aragat, Cary M.; Sumalinab, Erna P.; Bauyot, Marleonie M. (East Asian Journal of Multidisciplinary Research, 2024)
The pandemic has led researchers to reconsider traditional approaches, resulting in an increased dependence on digital platforms for data gathering, analysis, and dissemination. This qualitative study investigates the experiences and adaptations of Development Studies graduate and post-graduate students at Ateneo de Davao University in data gathering within a hybrid learning environment. The COVID-19 pandemic necessitated a shift from traditional face-to-face data collection methods to hybrid approaches, combining in-person and online learning modalities. Drawing on connectivism theory, the study explores how students navigate digital networks and adapt research methodologies to hybrid settings. Through Key Informant Interviews (KIIs), data were collected from three graduate and post-graduate students, focusing on modifications in data gathering strategies, challenges encountered, and comparisons with traditional methods. Thematic analysis revealed themes related to methodological changes, technological integration, and shifts in research experiences. While hybrid learning offers enhanced accessibility and flexibility, challenges include ensuring data reliability and addressing technological barriers.